Phylogeographic and genetic insights into Sinonychia martensi: an endemic cave-dwelling harvestman in Beijing - Ruoyi Xiao; Jingjing Zhao; Likun Zhao; Shahan Derkarabetian; Feng Zhang; Chao Zhang (BMC Ecology and Evolution)
Abstract Caves are one of the most exciting environments on earth, often considered an evolutionary laboratory due to the suite of convergent adaptive traits (troglomorphisms) of organisms inhabiting them. Sinonychia martensi Zhang & Derkarabetian, 2021, is the first and only Travunioidea species recorded in China and is endemic to Beijing, being known from multiple caves. However, nothing is known regarding its phylogeographic or evolutionary history. In this study, we assessed the species boundaries of S. martensi from nine caves using morphological and molecular methods to elucidate its phylogenetic position and genealogical relationships. We also investigated the genetic diversity, population genetic structure and demographic history of S. martensi to clarify the population-level relationships and make inferences about historical phylogeography. The results indicate that the species from different caves all belonged to S. martensi but represent different populations. These populations exhibit strong population structure and low genetic diversity. Cave populations may share a common ancestor and multiple independent invasions to different caves. The diversification within S. martensi was likely driven by climate change and subtropical evergreen broadleaf forests associated with the middle Miocene. This study highlights the need for further conservation efforts and exploration in Beijing caves.